EVALUASI KEBERHASILAN DAN PENERIMAAN SISTEM KEUANGAN DESA MENGGUNAKAN MODEL TERINTEGRASI DI KABUPATEN TABANAN - Apsari, Ni Wayan Nova; Suaryana, I Gusti Ngurah Agung; Wirajaya, I Gde Ary; Ratna Sari, Maria Meiatrix (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.01.TAHUN.2022DO - 10.24843/EEB.2022.v11.i01.p10, 2022)
This study aims to evaluation the success and acceptance of Siskeudes in Tabanan Regency using an integrated model (Built with the Delone and Mclean ISSM, UTAUT and HOT Fit). Variables in this study are human factors, technological factors, organizational factors, behavioral intentions, user satisfaction and net benefits. The study was conducted by distributing questionnaire links through the Whatsapp group of Siskeudes Operator Tabanan Regency. The method of determining the sample in this study was carried out by census in order to obtain 131 Respondents. The data analysis technique used Structural Equation Model (SEM) with Amos 16.00 software. The results showed that technology factors affect user satisfaction, user satisfaction affects net benefits, there is a compatibility relationship between humans and technology, humans and organizations and technology and organizations. However, human factors, technological factors and organizational factors have no effect on the intention to use Siskeudes. User intentions have no effect on user satisfaction and Net Benefit. The lack of user intention is because Siskeudes is a mandatory application so that it becomes a demand and routine in managing village finances.